GC-MS/MS-Based metabolite profiling and bioactivity studies of endophytic fungi from the medicinal plant Alternanthera philoxeroides (mart.) Griseb: GC-MS/MS-Based metabolite profiling and bioactivity studies (Bangladesh Journal of Scientific and Industrial Research, 2025)
Endophytic fungi have garnered significant scholarly interest among researchers worldwide over the past three decades, attributed to their identification as a boundless reservoir of structurally and biologically innovative compounds. This study sought to analyze the traits of endophytic fungi., alongside biological assessments such as antimicrobial and antioxidant assay, derived from the medicinal plant Alternanthera philoxeroides (Mart.) Griseb. Six distinct endophytic fungal strains were successfully isolated and characterized based on morphological criteria and identified at the genus level, of which three were classified as Carvularia sp., while the remaining strains were identified as Colletotrichum sp., Diaporthe sp. and Xylaria sp. Numerous extracts of these endophytic fungi exhibited robust antibacterial properties and notable antioxidant activities. Chemical screening conducted via TLC and GC-MS/MS analysis revealed the presence of multiple potentially valuable secondary metabolites within the crude fungal extracts. The findings of the present study corroborate the advantageous effects of fungal endophytes, thereby position them as invaluable sources of bioactive compounds.Bangladesh J. Sci. Ind. Res. 60(4), 225-250, 2025